Application of Palm Solid Waste Ash as A Ceramic Glazing Material - Caecilia Tridjata Suprabanindya; Himawan Tri Bayu Murti Petrus; Fariz Al Hazmi (Jurnal Sains dan Terapan Kimia, 2025)
The aim of this research is to develop a glaze from palm oil solid waste ash. Oil palm plants were chosen because the ash of palm fronds, stems and trees have not been utilized optimally, only used as organic fertilizer and material for making furniture. This research is applied research involving expertise in the field of fine arts, especially ceramic art and chemical engineering, with an inquiry-based research approach. Laboratory tests (EDX Report) were carried out so that the process of modifying the ash glaze formula could be carried out more accurately. The output of this research is the palm oil solid waste ash glaze formula/recipe and ash analysis table along with test pieces of ash glaze trial results and ceramic work prototypes. In practice, organic ash cannot be used alone, but must be mixed with other ingredients so that it can potentially be processed into glaze. The glaze formula used in this research contains different mixtures of ingredients. In this research, organic ash was mixed with soil (Sukabumi and Kebumen) and ready-to-use frit glaze (F.107 and F.3T). Next, the ash glaze is burned at cone temperatures 5 and 6 (1150 0C–1200 0C). The test piece material used is Sukabumi clay which has been proven to be compatible with the oil palm plant ash glaze formula, resulting in a more varied, attractive, artistic and unique visual appearance of the work.